Commercial microbial inoculants with PGPR on productive and economic variables of common bean (Phaseolus vulgaris L.) - Granda-Mora, Klever (2024)
Introduction. In Ecuador, there are few studies on the use of microbial inoculants for the sustainable production common bean (Phaseolus vulgaris L.). Objective. To evaluate the effect of inoculation with plant growth-promoting rhizobacteria (PGPR) on productive and economic variables of P. vulgaris. Materials and methods. The research was carried out at the La Argelia Experimental Station in Loja, Ecuador, from February to July 2022. Using loamy soil, the common bean cultivar “Mantequilla” was employed in a randomized complete block design with seven treatments and four replications each. The treatments were: T1) absolute control, T2) Bacillus subtilis, T3) Rhizobium leguminosarum bv. viciae, T4) Pseudomonas fluorescens + B. subtilis, T5) R. leguminosarum bv. viciae + B. subtilis, T6) R. leguminosarum bv. viciae + P. fluorescens + B. subtilis, and T7) chemical fertilization. The effect of the treatments on growth, development, and yield components in the evaluated cultivar was assessed. Additionally, an economic analysis of the application of beneficial microorganisms versus chemical fertilization was conducted. Results. Treatment T6 (R. leguminosarum bv. viciae + P. fluorescens + B. subtilis) shortened the phenological phases (days), promoted a higher number of nodules, emergence percentage, plant height, leaf area, number of pods per plant, weight of 100 seeds, nitrogen content, and agricultural yield without statistical differences (p<0.05) compared to chemical fertilization (T7). The economic analysis showed that T6 generated higher income and greater profitability compared to chemical fertilization. Conclusion. Inoculation with beneficial microorganisms positively affected the productive and economic variables of common beans and can be a valid alternative to the conventional use of chemical fertilizers.